Portal versus peripheral circulating tumor cells as prognostic biomarkers in patients with stage I–III pancreatic ductal adenocarcinoma - Prasoppokakorn, Thaninee; Chaiteerakij, Roongruedee; Buntho, Areeya; Ingrungruanglert, Praewphan; Israsena, Nipan; Rittitid, Wiriyaporn; Angsuwatcharakon, Phonthep; Mekaroonkamol, Parit; Kongkam, Pradermchai; Rerknimitr, Rungsun (Endoscopy, 2025)
The detection of portal venous circulating tumor cells (CTCs) may better reflect vascular metastasis and predict micrometastasis risk than peripheral blood in patients with pancreatic ductal adenocarcinoma (PDAC). We hypothesize that portal CTCs could better represent micrometastasis and can predict survival in PDAC patients.A single-center, prospective cohort study of patients with stage I–III PDAC was conducted. Portal venous blood was obtained via endoscopic ultrasound-guided sampling, and peripheral blood was collected on the same day. CTCs were detected using EpCAM and mucin1 antibodies and reported as cells/8 mL of blood.Among 35 patients, the portal and peripheral CTC detection rates were 94.3% and 82.9%, respectively. Advanced PDAC with locoregional metastasis had higher portal CTCs than less aggressive disease (P < 0.05), while peripheral CTCs showed no significant differences. During the 50-month follow-up, patients with portal CTCs ≥8 had poorer survival (6.1 vs. 19.0 months; P = 0.001) and patients with peripheral CTCs ≥3 also had poorer survival (4.6 vs. 14.2 months; P = 0.002). In multivariable analysis, both portal CTCs ≥8 and peripheral CTCs ≥3 showed significant adjusted associations with survival (adjusted hazard ratio 3.4 [P = 0.009] and 2.7 [P = 0.02], respectively).Higher CTC counts in both the portal and peripheral systems were significantly associated with poorer survival in stage I–III PDAC; however, only portal CTCs reflected tumor aggression and locoregional metastasis.